Peningkatan Kemampuan Motorik Kasar melalui Permainan Minecraft Run Pada Anak di TK Model - Rahmaningrum, Afifah; Kusumawardani, Cindy Tri; Dewi, Dwi Jayanti Kurnia; Khosibah, Salma Aulia (Fakultas Tarbiyah dan Keguruan UIN Antasari Banjarmasin, 2024)
Lack of gross motor stimulation, lack of utilization of supporting facilities, and limited physical activity outside the classroom are the causes of the achievement of children's gross motor skills not yet optimal. Therefore, the study aimed to improve children's gross motor skills through sensorimotor game activities Minecraft Run in Group A1 Sleman Model Kindergarten. This is a Classroom Action Research (CAR) with 18 research subjects. Consists of 8 boys and 10 girls. Data collection techniques used observation and documentation. In addition, the data analysis technique used is quantitative and qualitative descriptive analysis. The results showed that the Minecraft Run game significantly improved children's gross motor skills. The initial percentage of children's gross motor skills of 49.4% increased to 67.3% in cycle I and increased to 82.2% in cycle II. Minecraft Run is an effective method to integrate game-based learning with the stimulation of children's motor development.